Adverse Childhood Experiences (ACE), Adolescent Misconduct, and Violent Extremism: A Comparison of Former Left-Wing and Right-Wing Extremists - Logan, Michael K. (Terrorism and political violence, 2024)
The current paper compares the prevalence and nature of childhood adversity among twenty former left-wing and right-wing extremists. Findings from the Adverse Childhood Experiences (ACE) questionnaire suggest that exposure to childhood adversity was common in the early lives of both extremist types. For example, 50 percent of LWE and 70 percent of RWE experienced four or more ACE exposures during the first eighteen years of their life. The results also demonstrate that participants in both samples experienced a range of adolescent conduct problems. These conduct issues highlight the cascading effects of childhood adversity, where negative events help produce a downward spiral that ultimately increases a person’s susceptibility to extremism. Despite the relatively small sample, findings from this exploratory study build on the risk factor model of violent extremism by highlighting childhood adversity and adolescent misconduct as nonideological precursors to violent extremism among different types of extremists.